The Adverbial Phrase and Its Translation Found in the “Houseboy and Maid” - I Made Juliarta Juliarta (ITScience (Information Technology and Science), 2021)
This study intends to: (i) analyze the forms of adverbial phrases and their translation found in the data source, (ii) analyze the types of translation shifts of adverbial phrases in the translation process from the source language into the target language. This research study focuses on English adverbial phrase and their translations into Indonesian found in the story entitled “Houseboy and Maid.” This study aims to discover the forms of adverbial phrases found in the story “Houseboy and Maid” and the types of translation shifts in the translation process. In analyzing the data, the analysis uses the theory of adverbial phrase proposed by Brown and Miller (1991) and the theory of translation shift submitted by Catford (1965). Analyzing the data was started by reading the entire data source to understand the story and observe the possibility of the data source that it can take from the report entitled “Houseboy and Maid.” The method of collecting data is first; the data source is read to find out the forms of English adverbial phrases in syntactic structure. This research shows that most of the English adverbial phrase is translated into Indonesian using the theory of unit shifts and design proposed by Catford (1965). There are some forms of adverbial phrases found in the data source.